Epstein-Barr virus (EBV)-associated epithelial and non-epithelial lesions of the oral cavity - Kentaro Kikuchi; Harumi Inoue; Yuji Miyazaki; Fumio Ide; Masaru Kojima; Kaoru Kusama (Elsevier, 2017)
Epstein-Barr virus (EBV) is known to be associated with the development of malignant lymphoma and lymphoproliferative disorders (LPDs) in immunocompromised patients. EBV, a B-lymphotropic gamma-herpesvirus, causes infectious mononucleosis and oral hairy leukoplakia, as well as various pathological types of lymphoid malignancy. Furthermore, EBV is associated with epithelial malignancies such as nasopharyngeal carcinoma (NPC), salivary gland tumor, gastric carcinoma and breast carcinoma. In terms of oral disease, there have been several reports of EBV-related oral squamous cell carcinoma (OSCC) worldwide. However, the role of EBV in tumorigenesis of human oral epithelial or lymphoid tissue is unclear. This review summarizes EBV-related epithelial and non-epithelial tumors or tumor-like lesions of the oral cavity. In addition, we describe EBV latent genes and their expression in normal epithelium, inflamed gingiva, epithelial dysplasia and SCC, as well as considering LPDs (MTX- and age-related) and DLBCLs of the oral cavity.